2018
DOI: 10.1037/adb0000325
|View full text |Cite
|
Sign up to set email alerts
|

Food addiction prevalence and concurrent validity in African American adolescents with obesity.

Abstract: Food addiction, measured by the Yale Food Addiction Scale (YFAS), has been associated with obesity, eating-related problems (e.g., bingeing), and problematic consumption of highly processed foods. Studies on this topic have primarily examined adult samples with an overrepresentation of White individuals, and little is known about addictive-like eating in adolescents, particularly African American adolescents who exhibit high rates of obesity and eating pathology. The current study examined the prevalence of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 65 publications
9
41
0
Order By: Relevance
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of FA as determined using the YFAS‐C has been reported in 18 publications 24,28–32,34–39,41,42,45–48 (Table 2). The meta‐analysis estimated an overall FA prevalence at 15% (95% CI: 11–19%) among children and adolescents, with an I 2 of 95.64%.…”
Section: Resultsmentioning
confidence: 99%
“…It has been theorized that overeating may have addictive qualities , and there is a growing body of literature which reports that craving for drugs and drive for food involve similar hypothalamic pathways as seen on functional MRI (fMRI) studies . Recent studies have reported that 5.9–30.7% of adolescents with overweight and obesity enrolled in weight management interventions endorse addictive‐like eating habits, similar to the 15–19% reported by adults seeking obesity treatment . Interestingly, few weight management interventions have tested therapeutic techniques founded in addiction medicine principles to date, targeted towards adolescents .…”
Section: Introductionmentioning
confidence: 99%
“…In a nonclinical sample of Chinese adolescents, YFAS‐C scores were associated with increased binge eating (i.e., consuming an objectively large amount of food plus loss of control; Chen, Tang, Guo, Liu, & Xiao, ). In adolescents with overweight and obesity, YFAS‐C scores have also been associated with binge eating as well as overeating (i.e., consuming an objectively large amount of food without a loss of control), elevated cravings, greater attentional and motor impulsivity, and higher BMI (Meule, Müller, Gearhardt, & Blechert, ; Schulte, Jacques‐Tiura, Gearhardt, & Naar, ). Finally, in a group of Dutch adolescents in an inpatient psychiatry unit, scores on the YFAS‐C have been associated with increased hunger and disinhibition (Albayrak et al, ).…”
Section: Introductionmentioning
confidence: 99%